2006
DOI: 10.1037/0022-3514.90.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Positive affect and the experience of meaning in life.

Abstract: Six studies examined the role of positive affect (PA) in the experience of meaning in life (MIL). Study 1 showed strong relations between measures of mood, goal appraisals, and MIL. In multivariate analyses, PA was a stronger predictor of MIL than goal appraisals. In Study 2, the most consistent predictor of the experience of meaning in a day was the PA experienced that day. Later, global MIL was predicted by average daily PA, rather than average daily MIL. Study 3 demonstrated no prospective relations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
694
3
18

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 940 publications
(753 citation statements)
references
References 53 publications
38
694
3
18
Order By: Relevance
“…Given that individuals who find their lives meaningful perceive their lives as being satisfactory (Jia-Yang, Wong, Joubert, Lai, & Wan, 2008;Kashdan & Steger, 2007), a negative correlation between neuroticism and the presence of meaning in life is not inexplicable. This study also found that positive affect predicts the presence of meaning in life, as do similar studies (Hicks & King, 2007;King et al, 2006;King & Hicks, 2009). Positive affect influences cognition in a way that eases the nature of meaning and assists in the exploration of meaning.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Given that individuals who find their lives meaningful perceive their lives as being satisfactory (Jia-Yang, Wong, Joubert, Lai, & Wan, 2008;Kashdan & Steger, 2007), a negative correlation between neuroticism and the presence of meaning in life is not inexplicable. This study also found that positive affect predicts the presence of meaning in life, as do similar studies (Hicks & King, 2007;King et al, 2006;King & Hicks, 2009). Positive affect influences cognition in a way that eases the nature of meaning and assists in the exploration of meaning.…”
Section: Discussionsupporting
confidence: 64%
“…According to Gençöz (2000), a positive affect is "active pleasure and joy one finds in life, " and a negative affect is "the activation of unpleasant affects such as stress, fear, and anger. " Studies about the concept of meaning in life and personal affects (King et al, 2006;King & Hicks, 2009) suggest that positive affects provide are the primary contributors to the perception of meaning in life, and that situations characterized by positive affects could serve as a "natural habitat" for meaning in life. They also imply that negative affects are triggered when individuals' needs for meaning in life are not satisfied (Maddi, 1970;Pan, Wong, Joubert, & Chan, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both types of well-being share some common sources (e.g., perceived social connections) (29) and can reciprocally influence one another (29) [i.e., positive affect predisposes people to find positive meaning (43,44), and finding positive meaning increases positive affect (45)]. As such, the current finding that a purified index of eudaimonic well-being (purged of shared variance with hedonia) predicts a more favorable pattern of gene expression than does a purified index of hedonic well-being (purged of shared variance with eudaimonia) says more about which form of well-being one would not want to do without, rather than which form one would be better to avoid.…”
Section: Discussionmentioning
confidence: 99%
“…Personal-nostalgia inductions typically (Batcho, 2013;Cheung et al, 2013 rather than by increasing work meaning? This is a pertinent question in light of evidence that (dispositional) PA is correlated with meaning in life (Hicks, Trent, Davis, & King, 2012;King, Hicks, Krull, & Del Gaiso, 2006;Trent, Lavelock, & King, 2013;Steger et al, 2013).…”
Section: Study 2: Testing the Effect Of Organizational Nostalgia On Wmentioning
confidence: 99%